Beyond income: Exploring the role of household wealth for subjective well-being in Germany - Antje Jantsch; Julia Le Blanc; Tobias Schmidt (Journal of Happiness Studies, 2024)
An individual's financial situation positively impacts her subjective well-being (SWB) according to the literature. However, most existing studies focus solely on income, neglecting other aspects of an individual's financial situation such as wealth. In this paper, we empirically examine the relationship between SWB, income, household wealth, and its components. Additionally, we explore the significance of one's wealth relative to others' for SWB. Our contribution expands the limited literature on absolute and relative wealth and SWB by utilizing unique microdata from a German wealth survey, the German Panel on Household Finances (PHF). Our findings indicate that both assets and debts, alongside income, are associated with an individual's SWB. In particular, a similar relative increase in financial assets is associated with a greater increase in SWB than the same percentage increase in real assets, and SWB decreases as the level of unsecured debt increases. Furthermore, individuals tend to experience decreased SWB when comparing themselves to others with more assets or less debt. Interestingly, we observe divergent effects of relative wealth on SWB among younger and older individuals. These results underscore the significance of considering wealth, in addition to income, when analyzing determinants of SWB.
Keywords: I31; D19; D31; 330; relative wealth; debt; assets; subjective well-being; relative deprivation; tunnel effect